1998
DOI: 10.1177/002215549804600805
|View full text |Cite
|
Sign up to set email alerts
|

Carbocyanine Postmortem Neuronal Tracing: Influence of Different Parameters on Tracing Distance and Combination with Immunocytochemistry

Abstract: Carbocyanines (DiI, DiA, DiO) are able to travel along membranes by diffusion and therefore have been used as postmortem neuronal tracers in aldehyde-fixed tissues. Surprisingly, detailed data on the influence of different parameters on tracing distances are still missing. This study was carried out to optimize tracing procedures and to reveal the validity of the combination of postmortem tracing with immunocytochemistry. Carbocyanine crystals were applied to the cervical spinal cord, sciatic nerves, and brach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
56
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 32 publications
6
56
1
Order By: Relevance
“…Although DiI can be used to label fixed tissue, the distance DiI travels in the fixed spinal cord plateaus at around 2.9 cm after 12-15 weeks in humans and guinea pigs (Lukas et al 1998). We have confirmed that DiI is an excellent postmortem tracer in rat spinal cord.…”
Section: As An Anterograde Tracer In Spinal Cord Regeneration Stusupporting
confidence: 66%
“…Although DiI can be used to label fixed tissue, the distance DiI travels in the fixed spinal cord plateaus at around 2.9 cm after 12-15 weeks in humans and guinea pigs (Lukas et al 1998). We have confirmed that DiI is an excellent postmortem tracer in rat spinal cord.…”
Section: As An Anterograde Tracer In Spinal Cord Regeneration Stusupporting
confidence: 66%
“…Extending incubation times beyond 6 weeks appeared to have no consistent effect on the degree of labeling although this parameter can be important for visualizing projections (Lukas et al, 1998;Sparks et al, 2000). Perhaps myelination is more advanced for projections to the contralateral IC than for ipsilaterally projecting axons (e.g., sequential myelination of corpus callosum, Looney and Elberger, 1986; differential myelination of spinal tracts, Hamano et al, 1998) and, thus, interferes with DiI confusion or detection.…”
Section: Labeling and Histologymentioning
confidence: 96%
“…For this, we performed anterograde labeling of thalamic axons with the lipophilic dialkylaminostyryl dye (DiA) as an alternative approach. Labeling in living tissue is 6 mm/day faster than in fixed tissue (0.2-0.6 mm/day) due to active dye transport (Lukas et al, 1998). Thus, we injected DiA into the thalamus of freshly prepared brains at E13.5, which were then kept in culture for 10 h. After fixation, the tissue was stored for 7 days at 37°C to ensure complete axonal labeling.…”
Section: Ephrin A5 Is Expressed In Thalamic Axonsmentioning
confidence: 99%